Aircraft structures for engineering students - Megson, T. H. G. (Thomas Henry Gordon) (Oxford ; Waltham, MA : Butterworth-Heinemann, 2013)
Aircraft Structures for Engineering Students is the leading self contained aircraft structures course text. It covers all fundamental subjects, including elasticity, structural analysis, airworthiness and aeroelasticity. Now in its fifth edition, the author has revised and updated the text throughout and added new examples and exercises using Matlab(c). Additional worked examples make the text even more accessible by showing application of concepts to airframe structures. Includes a Solutions Manual available to all adopting teachers. * New worked examples throughout the text aid understanding and relate concepts to real world applications * Matlab examples and exercises added throughout to support use of computational tools in analysis and design * An extensive aircraft design project case study shows the application of the major techniques in the book * More end of chapter exercises, with an accompanying Solutions Manual (for instructors only) at http://textbooks.elsevier.com.
Part A: Fundamentals of Structural Analysis A1 Elasticity A2 Virtual Work, Energy and Matrix Methods A3 Thin Plate Theory A4 Structural Instability A5 Vibration of Structures Part B Analysis of Aircraft Structures B1 Principles of Stressed Skin Construction B2 Airworthiness and Airframe Loads B3 Bending, Shear and Torsion of Thin-Walled Beams B4 Stress Analysis of Aircraft Components B5 Structural And Load Discontinuities B6 Introduction to Aeroelasticity.
Includes bibliographical references and index.
Keywords: Airframes; Structural analysis (Engineering); Electronic books